Influence of Choline-Based Ionic Liquids as Neoteric Green Solvents on Aqueous Solubility of Lamotrigine and Piroxicam Drugs - Hemayat Shekaari; Negar Basteholia; Masumeh Mokhtarpour; Mohammed Taghi Zafarani-Moattar (Tabriz University of Medical Sciences, 2022)
Background: New compounds called choline-based ionic liquids (ILs) that are environmentally friendly have become more attractive. In this study, some choline-based ILs (choline lactate (ChLa) and choline propionate (ChPro)) have been used to increase the aqueous solubility of lamotrigine (LTG) and piroxicam (PXM) at T = 298.15 to 313.15 K. Methods: ILs were prepared and purified. The solubility of drugs in the aqueous ILs solutions was measured at different temperatures with shake flask method. Results: The solubility of the investigated drugs increased with increasing the weight fraction of ILs. The solubility data were correlated by e-NRTL, Wilson, Apelblat and λh (Buchowski) models. Conclusion: The aqueous solubility of drugs depends on both the weight fraction of co-solvents and the solution temperature. These two essential parameters were analyzed through some semi-empirical and activity coefficient models getting the average relative deviation percent as e-NRTL (3.09%) < Wilson (3.92%) (for full range concentration of co-solvent) and Apelblat (3.52%) < λh (Buchowski) (5.11%) (for the dilute region of co-solvent). In addition, the results show that the aqueous solubility increases with rising temperature and there are strong interactions between the drug and the ILs.